COMORBIDITY: APAKAH MERUPAKAN FAKTOR RISIKO INFEKSI LUKA OPERASI PASCA SEKSIO SESAREA? - Remilda Armika Vianti (LPPM Universitas Pekalongan, 2015)
The surgical site infection is one of the effect nosocomial infection in Indonesia. The prevalence of surgical site infection in Indonesia was 2-18%. The case of surgical site infection post cesarean section was 15%. Surgical site infection post-cesarean section may increase mortality and morbidity, length of stay and cost of hospitalization. Surgical site infection may decrease risk factors especially risk factors for surgical site infection post cesarean. The aim this research is to correlated anemia with surgical site infection post-cesarean section. This study was an observational analytical study. Retrospectif case control design was used in this study with quantitative approach. The diagnosis of surgical site infection was defined according to the criteria of the Centers for Disease Control and Prevention (CDC). The bivariat analysis used independent T-test and Chi-square. The results that the surgical site infection were identified in 311 (19%) of 1,592 women having been through caesarean section. The result of bivariat analysis showed that the factors significant suppoting surgical site infection, anemia in 117 patient (18,8%), infection were identified in 69 (22,2%) [OR=1,56 (1,04-2,35)]. The samples studied from 2011, 2012 and 2013 through the medical records of patients. Experienced caesarean section with several risk factors have not been well documented. Detection of unknown incidence of infection when patients back control documented in the medical record outpatients. Keywords: surgical site infection, cesarean section, risk factors.